Ethanol gas sensing with lower temperature and higher response based on three-dimensional multilevel materials composed of micron hollow carbon spheres@SnO2 nanoparticles. (August 2022) - Huang, Zehua; Wang, Weizhe; Xiao, Debiao; Mo, Yuzhi; Wang, Shuangbao; Xu, Zhimou; Peng, Jing
Abstract: Metal oxide semiconductor gas sensors (MOS) based on tin oxide have excellent performance in ethanol gas detection and have been widely used in industrial production, environmental protection, and road safety detection. However, conventional tin oxide sensors can only show excellent detection performance for ethanol gas above 250 °C. In this work, nano-size tin oxide particles were grown on the micron hollow carbon spheres derived from the biomaterial chlorella by a gel method. This three-dimensional hierarchical porous structure can enrich ethanol gas at a certain temperature. Ethanol gas sensor fabricated with this material has better sensing performance at low temperature (168–200 °C). Graphical Abstract: ga1 Highlights: The material has a 3D multilevel structure with both micro-holes and nano-holes. Micron hollow carbon spheres frameworks were prepared with biomaterials. Micro-nano composite structure enhances the ethanol gas sensing performance of SnO2 . A new mechanism is proposed for micro-nanocomposite structure in gas enrichment.